Petrology And Geochemistry Of Selected Nepheline Syenites From Malawi And Their Potential As Alternative Potash Sources - Chiwona, Annock; Cortés, Joaquín; Gaultona, Rachel; Manning, David (My University, 2022)
The Sub Saharan Africa agricultural sector is one of the most disadvantaged regions, partly due to high fertilizer import costs from the northern hemisphere. Malawi is one such country which faces these fertilizer challenges for the agricultural sector growth and food crop production. However, Malawi has numerous intrusive alkaline rocks, nepheline syenites, especially within the Chilwa alkaline province. This study was therefore conducted to assess these nepheline syenites for their potential as potassium sources. We used Malawi's new airborne geophysical gamma ray data acquired in 2013, coupled with satellite remote sensing, to identify nepheline syenites suitable as possible sources for alternative silicate K-fertilizer, and carried out geochemical analysis of whole rock samples. Results show that the K2O content for the nepheline syenites varies from 3.17 wt % to 9.14 wt % with an average of 5.22 wt %. The K2O/Na2O ratio for Malawi's nepheline syenites ranges from 0.41 to 1.28 with an average of 0.65 showing that the nepheline syenites are mostly sodic but with variable composition. In addition to nepheline, the calcium feldspathoid davidsmithite ((Na,Ca)AlSiO4) was identified in the syenites using scanning electron microscopy with energy dispersive analysis. Although the different intrusive complexes are not homogenous, our results show that, generally, the nepheline syenites from Malawi have similar geochemistry and mineralogical composition to those which have been used as crushed-rock fertilizers in other parts of the world.
Keywords: Potassium; Igneous and Metamorphic Petrology; Geophysical gamma ray spectrometry